KHI Objectivation: Study of Female Marriage Guardians Progressive Maqasid Syariah Perspective - Bella, Sinta; Al-Asyari, M. Khoirul Hadi (Proceeding International Conference on Religion, Science and Education, 2025)
The marriage guardian is one of the mandatory marriage pillars fulfilled, as found in Hadith, Laws, and also the Compilation of Islamic Law, however in possible KHI settings become marriage guardian is a man just like that in article 20 paragraph 1 compilation of Islamic law. However, reality in society someone implemented a draft female marriage guardian, even though the No by article 20 paragraph 1 Compilation of Islamic Law, as ever told by Kh Imam Nakhai (teacher Ma’had Aly Situbondo and Commissioner National Commission Women in Indonesia). the method used is normative with approach laws and studies References or library research and content analysis for explaining female marriage guardians in KHI with phenomenon existing reality about female marriage guardians in Indonesia. the theme raised is "Objectification KHI: Perspective Study of Female Marriage Guardians Progressive Maqasid Sharia " In the study there are two important questions, First How to draft female marriage guardians in KHI?, and the second How KHI objectification of female marriage guardians in perspective maqasid sharia Jasser Auda? Research results This shows that KHI’s objectification regarding marriage guardians required a man to be refuted If seen from the corner of Maqasid Sharia Jasser some implement it draft justice To reach benefit people as Grace lil natural.